? Are Kids Mentally Smart or Because of Technology - Al-Hawamdeh, Mekhled Alayyan; Abu Nawas, Mousa Khaleel (Journal of Educational and Psychological Sciences, 2020)
This research explores the influence of technology on smartness & cognitive development of children with analyzing the behavior of children with using the gadgets and advanced devices. It investigates whether the mental capabilities of children are due to use of technological equipment and tools or they have their own abilities. The research uses mixed approach method questionnaire and survey approach with convenience sampling from 15 respondents from Al Ain basic cycle schools, three of them were selected for an interview. Results indicated that children nowadays are moving towards the age where parents will make their children bounded with these technologies and limiting their thinking capabilities to solve the complex matters and issues that surely will make children dumb instead of making smarter. The researcher recommended that it is important for parents, teachers, professional, healthcare providers and students to set specific goals for children and use of technology that will support efforts of children to meet their goals in life. They are required to monitor the children and guide them to make effective and efficient utilization of these technologies that can improve their mental capabilities, and also involve some physical activities that can make the children smarter than the basis of technology.
Keywords: gadgets; palmtops; Smartphone; collaboratively